Analisis Layanan Teknologi Komunikasi Klinik Fisioterapi Siti Hajar Era Revolusi Industri 4.0 - Lagut Sutandra; Sulaiman Sulaiman (Program Studi Sistem Informasi, 2019)
Communication technology 4.0 industrial revolution is an era where the wider community has become accustomed to the use of the internet and digital as an instrument facilitates daily activities. This research uses the SWOT analysis, where the object of research is the clinic manager and information obtained through interview techniques which are then processed to determine EFAS and IFAS. This research aims to look at the role of the intended communication technology for health services in the Physiotherapy Clinic of Siti Hajar. The results of this research are based on the SWOT analysis carried out in this study, which found that Physiotherapy Clinics must carry out Weakness - Treath (WT) strategies or defensive strategies, namely trying to suppress weaknesses in internal clinics and avoid threats to external clinics. The conclusion of this research is that the program must focus on improving the clinical management of human resources in terms of industrial revolution 4.0 communication technology and implementing education or learning for physiotherapy service users.Keywords: Communication Technology, Revolution Industry 4.0, Physiotherapy Clinic